STUDI TERMAL PADA SEGMEN CETAKAN CROWN PADA MESIN CURING DALAM PROSES PRODUKSI BAN MOBIL DI PT. ELANG PERDANA TYRE INDUSTRY - Christofel Jarot Yudaputranto; Sandy Suryady (Jurnal Ilmiah Teknik, 2025)
The curing process is a stage in car tire molding carried out under high temperature and pressure. One of the key components in this process is the crown mold segment, which functions to shape the tread pattern on the tire. This study aims to analyze the heat distribution in the crown mold segment using Solidworks software, focusing on material specifications, heat distribution patterns, and simulation parameters affecting the results. The material used is Steel AISI 1020. The simulation results indicate an even heat distribution with an initial temperature of 453 K, convection ranging from 179.933°C to 179.967°C on the side area, and 179.916°C to 179.950°C on the tread pattern. Heat transfer rates were recorded as 96,323.28 W through conduction, 898.452 W through convection, and 2.56 W through radiation. Key parameters influencing the simulation include the initial material temperature (453 K), convection coefficient (10 W/(m²·K)), radiation emissivity (0.3), and ambient temperature (300 K).